A new species of Passalus Fabricius, 1792 (Coleoptera: Scarabaeoidea: Passalidae) from Sierra Nevada de Santa Marta, Colombia - Jiménez-Ferbans, Larry; Amat-García, Germán; Reyes-Castillo, Pedro (Instituto de Ecología, A.C., 2012)
Passalus (Pertinax) unimagdalenae sp. n. is described and illustrated as a mountain species distributed between 1560 and 2309 masl in the Sierra Nevada de Santa Marta.